CASE STUDIES METHOD IN MEDICAL SCHOOL - Reseda M. Garanina; Andrey A. Garanin (Высшее образование в России)
The paper touches upon the use of active forms of training at medical university, particularly the method of case analysis. The authors present the methodological basis of case studies method and an algorithm of lessons with the use of modern educational classifications of medical cases. The sequence of stages of student's productive activity in a problematic